A rare case of Sister Mary Joseph nodule as the only sign of unknown primary malignancy - Lanjewar, Sunil M.; Nandagawali, Vishal; Sagrule, Dhiraj; Lavankar, Pratik; Surana, Kuntal M.; Khuje, Praful; Bhalerao, Sagar (International Surgery Journal, 2016)
Sister Mary Joseph nodule or Sister Mary Joseph Sign refers to a palpable nodule bulging into the umbilicus as a result of metastasis of a malignant cancer in the pelvis or abdomen. We report a rare case of umbilical mass as the only presenting sign in an old age woman confirmed by CT scan and true cut biopsy to be malignancy. The primary tumor for the umbilical mass or Sister Mary Joseph nodule was not found in this case, although possibility of gynaecological tumor is very high.